Demand Reduction and Preemptive Bidding in Multi-Unit License Auctions - Jacob Goeree; Theo Offerman; Randolph Sloof (Tinbergen Institute, 2004)
Multi-unit ascending auctions allow for equilibria in which bidders strategically reduce their demand and split the market at low prices. At the same time, they allow for preemptive bidding by incumbent bidders in a coordinated attempt to exclude entrants from the market. We consider an environment where both demand reduction and preemptive bidding are supported as equilibrium phenomena of the ascending auction. In a series of experiments, we compare its performance to that of the discriminatory auction. Strategic demand reduction is quite prevalent in the ascending auction even when entry by the newcomer imposes a (large) negative externality on incumbents. As a result, the ascending auction performs worse than the discriminatory auction both in terms of revenue and efficiency, while the two auction formats offer similar chances for newcomers to enter the market.
Keywords: D44; D45; C91; 330; Multi-license auctions; demand reduction; external effects; preemption; Auktion; Auktionstheorie; Konzession; Nachfrage; Test